Improved Optimization Study of Integration Strategies in Solar Aided Coal-Fired Power Generation System - Rongrong Zhai; Miaomiao Zhao; Chao Li; Pan Peng; Yongping Yang (International Journal of Photoenergy)
Solar aided coal-fired power generation system (SACFPGS) combines solar energy and traditional coal-fired units in a particular way. This study mainly improves the solar thermal storage system. Genetic algorithm is used to optimize the SACFPGS. The best integration approach of the system, the collector area, and the corresponding thermal storage capacity to replace each high-pressure extraction are obtained when the amount of coal saving in unit solar investment per hour is at its largest. System performance before and after the improvement is compared. Results show that the improvement of the thermal storage system effectively increases the economic benefit of the integrated system.